A critical analysis of the opinions of Daily Voice readers about the South African Defence Force (SANDF) in 2015 and 2019 - O'Connell, Siona (University of Pretoria, 2021)
Dissertation (MA (Historical and Heritage Studies))--University of Pretoria, 2021.